Economia informal no Brasil: aspectos de inserção, permanência e transição no mercado de trabalho metropolitano - Guilherme Issamu Hirata (2007)
This dissertation investigates informal economy in Brazilian metropolitan areas. There are two main objectives: to investigate personal attributes of the informal workers (defined as self-employed and employer employing up to five workers) and to verify who of those make a transition out of that occupation. The results point that individuals who are in a state of vulnerability in the labor market, such as low-education individuals and female household heads, have higher probability to become informal workers than the others. About transition, the results show that entrepreneurship time and economic performance are more important than personal attributes on the probability of staying in the informal economy.